PENGARUH LINGKUNGAN TERHADAP KESEHATAN MENTAL YANG MENYEBABKAN KELAHIRAN PREMATUR: LITERATUR REVIEW - Nazwa Fatin Oktariani; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
Prematurity is a cause of death in toddlers which takes quite a lot of victims. This happens because pregnant women can be triggered by various aspects such as environmental influences. Various studies show that the environment can have an influence on pregnant women as well as on the fetus. Not a few mothers are victims of death, and the impact of preterm birth on children who are born prematurely can hamper growth and development at a later date. This research aims to determine the extent of environmental influence on premature birth, which was collected from several published articles. The method used for this research is a Literature Review which collects several articles that have been published. Prematurity is an event that often occurs in developed and developing countries, therefore pregnant women need to be treated and given better attention. There are several things that can cause prematurity, one of which is maternal health factors including: Preeclampsia, infectious diseases such as the urinary tract, stress, lack of nutrition, and many more and there are also symptoms of premature birth, one of which is low back pain, lower abdominal cramps, nausea and vomit.